2021
DOI: 10.4314/tjs.v47i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Responses of Smallholder Farmers to Climate Change Effects in Semiarid Areas of Bahi and Kongwa Districts, Tanzania

Abstract: This study examined the vulnerability and responses of smallholder farmers to climate change effects in Semiarid Areas of Bahi and Kongwa Districts. A total of 366 household heads were involved in this study. The study employed questionnaire, interviews and documentary review as data collection techniques. Archival data for temperature, rainfall and crop yields were collected for trend analysis. Descriptive and inferential statistics were used to analyse quantitative data, content analysis was employed to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The study has revealed the presence of unreliable rainfall patterns and an increase in maximum temperatures in the study area. Many other studies have documented similar observations in parts of Tanzania, like Dodoma, Dar es Salaam, and Singida (Mlozi et al 2014;Mwamfupe 2014;Myeya 2021). The reliance on rainfall makes rain-fed agriculture vulnerable to climate change.…”
Section: Changes In Rainfall and Temperature In The Study Areamentioning
confidence: 65%
“…The study has revealed the presence of unreliable rainfall patterns and an increase in maximum temperatures in the study area. Many other studies have documented similar observations in parts of Tanzania, like Dodoma, Dar es Salaam, and Singida (Mlozi et al 2014;Mwamfupe 2014;Myeya 2021). The reliance on rainfall makes rain-fed agriculture vulnerable to climate change.…”
Section: Changes In Rainfall and Temperature In The Study Areamentioning
confidence: 65%
“…Similar findings (MacLeod, 2018;Omay et al, 2023) in other East African countries show that the earliest average end dates for the March, April, and May seasons were recorded as 26th Apr, 03rd May, and 17th May in lower eastern and northern Kenya, southeastern Ethiopia, most of Somalia, respectively. In other semi-arid regions of Tanzania, studies show the onset and cessation were found to be unpredictable (Myeya & Mulungu, 2021).…”
Section: Onset Cessation and Season Length In Bahi And Mpwapwamentioning
confidence: 99%
“…Since the nation is one of those most severely impacted by climate change, creative approaches to mitigating its effects are essential, particularly in drylands where, according to recent estimates, vulnerabilities, hazards, and impacts are greatest (IPCC, 2022;Mdemu, 2021). Examples of the unprecedented increase in smallholder farmers' vulnerability include irregular planting dates and variations in the sizes of planted and harvested plots (Ayanlade et al, 2022;Myeya, 2021).…”
Section: Introductionmentioning
confidence: 99%